The Effects of Lactobacillus plantarum, Bacillus subtilis, a Lignocellulolytic Enzyme System, and Their Combination on the Fermentation Profiles, Chemical Composition, Bacterial Community, and In Situ Rumen Digestion of Fresh Waxy Corn Stalk Silage - Jiaqi Su; Ye Xue; Kunlun Zhang; Zihan Liu; Jingyi Lv; Qi Yang; Zhongqiu Li; Chunlong Liu; Hangshu Xin (Animals, 2024)
The objective of this study was to assess the impact of Lactobacillus plantarum, Bacillus subtilis, and a lignocellulolytic enzyme system on the nutritional value, fermentation profiles, rumen digestion, and bacterial community of fresh waxy corn stalk silage. Fresh waxy corn stalks harvested after 90 days of growth were treated with no additives (CON), compound multiple lactobacilli (ML, comprising Lactobacillus plantarum at 1.0 × 105 cfu/g fresh weight and Bacillus subtilis at 1.0 × 105 cfu/g fresh weight), a lignocellulolytic enzyme system (LE, at 500 g/t), and a combination of the lignocellulolytic enzyme system and multiple lactobacilli (MLLE). Throughout the fermentation process, the contents of dry matter (DM) and water-soluble carbohydrates (WSC), as well as the counts of lactic acid bacteria, yeast, and mold, continuously decreased with the extension of the fermentation time. In contrast, the concentrations of acetic acid, propionic acid, and ammonia N progressively increased over time. Notably, the pH initially decreased and then increased as fermentation progressed, while the lactic acid concentration first increased and then decreased with the extension of the fermentation time. After 45 days of fermentation, the DM contents of LE and MLLE were significantly lower than that of CON, while the WSC content of MLLE was significantly higher than that of CON. LE most effectively increased the ED of DM and neutral detergent fiber (NDF). Compared to ML and LE, MLLE showed a greater increase in the “a” value of DM and NDF. The DM content in LE and MLLE was lower than in CON, with a higher WSC content. Both ML and MLLE produced more lactic acid than CON and LE, resulting in a lower pH in these groups. Additionally, the acetic acid content and ammonia N content were lower in ML and MLLE compared to CON and LE. The counts of lactic acid bacteria, yeast, and mold declined over the fermentation period, dropping below detectable levels on the seventh and fifth days, respectively. Relative to CON, the three additives reduced the relative abundance of Weissella and Klebsiella and increased that of Lactobacillus. In conclusion, LE improved the nutritional value and rumen digestion of the silage, ML enhanced its fermentation profiles and bacterial community, and MLLE significantly improved the nutritional value, rumen digestion characteristics, fermentation profiles, and bacterial community of the fresh waxy corn stalk silage.